NEW ANALYSIS OF VISUALIZATION IN EDUINFORMATICS USING A NETWORK WITH PARAMETRIC AND NONPARAMETRIC CORRELATION COEFFICIENTS WITH THRESHOLD - Takamatsu, Kunihiko; Kozaki, Yasuhiro; Muarakami, Katsuhiko; Bannaka, Kenya; Mitsunari, Kenichiro; Nakata, Yasuo (PEOPLE: International Journal of Social Sciences, 2018)
Eduinformatics, a new term coined by us, is a field that combines education and informatics, and novel techniques will need to be developed for this field. Earlier, we developed a new visualization method to visualize the curriculum of Kobe Tokiwa University using multidimensional scaling (MDS) and a scatter plot. In this study, our focus is on methods to analyze the relationships between answers to questions in eduinformatics questionnaires. MDS methods are very useful, but have limitations in that their results are difficult to interpret. To facilitate the interpretation of these results, we develop a new visualization method using a network with both parametric and non-parametric correlation coefficients with a threshold (VNCC). VNCC has nine steps. We apply the VNCC method to research on nursing education, and provide an example of the visualization of the result. VNCC methods will be useful in dealing with qualitative research in eduinformatics.